THE ROLE OF DISCIPLINE, ORGANIZATIONAL CLIMATE, PLACEMENT AND MOTIVATION IN IMPROVING THE PERFORMANCE OF STATE CIVIL SERVICES (ASN) IN THE DEPARTMENT OF LIBRARY AND REGIONAL ACCEPTANCE OF BANTEN PROVINCE - Encep Saefullah (Yayasan Education and Social Center, 2021)
This study aims to determine the role of Discipline, organizational climate, placement, and motivation in improving the State Civil Apparatus (ASN) performance at the Regional Library and Archives Service of Banten Province.The research method used is the quantitative analysis and associative descriptive to test the relationship and the amount of influence contribution between each variable. The number of samples in this study was the entire population, amounting to 69 State Civil Servants (ASN) at the Regional Library and Archives Service of Banten Province.The research results show that Discipline, organizational climate, placement, and motivation have a role, both about or contributing to a positive and significant influence in improving the Performance of the State Civil Apparatus (ASN) at the Banten Province Regional Library and Archives Service